SPECTACLE AND CARNIVAL IN DELILLO’S UNDERWORLD PROLOGUE (Philological Studies, 2019)
Starting from Debord’s definition of spectacle, Bakhtin’s views on carnival and carnivalisation in literature, and relevant later interpretations of these ideas, the paper examines and analyses the Prologue of Don DeLillo’s Underworld– an elaborate, though fragmented account of a famous baseball game in 1951, represented as a symbolic milestone in the recent American history and culture. Drawing on Bakhtin’s theory, a chronotope of carnival is conceived and applied as a framework for a reflection on possible meanings and wider implications of various details, stylistic and narrative devices used in the novel’s Prologue (and in the story “Pafko at the Wall”, the earlier version of the Prologue). In the light of Bakhtin’s idea about transposition of the “language” of carnival on the language of literature, equivalents of carnivalesque elements and categories are shown and analysed. However, while the Prologue might be read as an example of the carnivalisation of a spectacle, the importance of the theme of an always open and undecidable competition between spectacle and carnival will be explored and stressed, too.
Keywords: Don DeLillo, Underworld, “Pafko at the Wall”, spectacle, carnival, carnivalisation, chronotope